Lack of Methylene Blue Staining in Superficial Epithelia as a Possible Marker for Superficial Lateral Spread of Bile Duct Cancer. Issue 1 (1996) - Maetani, I.; Ogawa, S.; Sato, M.; Igarashi, Y.; Sakai, Y.; Shibuya, K.
Abstract : Longitudinal cancer spread is very important for staging of resectability in bile duct cancer. We verified the difference in methylene blue staining properties between cancerous and noncancerous epithelia that are usually observed by cholangioscopy. We obtained 45 biopsy specimens from the common bile duct of 20 patients with bile duct disease using percutaneous transhepatic cholangioscopy (PTCS) after staining with 0.05% methylene blue. We compared the microscopic staining properties with the gross endoscopic observations and evaluated the characteristics of methylene blue staining on frozen sections of each type of cholangial epithelium. Microscopic staining properties were significantly associated with endoscopic observations ( p = 0.00001). While 18 of 20 (90%) specimens of normal epithelia stained with methylene blue, 11 of 16 (69%) specimens of metaplastic epithelia were stained, with no staining obtained in cancerous epithelia. The cancerous epithelia stained significantly less often than either the normal ( p = 0.000005) or the metaplastic ( p = 0.001) epithelia. Evaluation of methylene blue staining during PTCS revealed that this stain was absorbed by the cholangial epithelia, not superficially stuck to it. The difference in methylene blue staining properties between the cancerous and normal epithelia could be helpful to clarify the boundary of superficial lateral spread of bile duct cancer.